To ensure that the second equation has an infinite number of solutions with the equation \( 6x + 3y = 9 \), it must represent the same line.
First, let's rewrite the given equation in slope-intercept form (i.e., \( y = mx + b \)).
-
Start with the equation:
\[
6x + 3y = 9
\]
-
Isolate \( 3y \):
\[
3y = 9 - 6x
\]
-
Divide by 3:
\[
y = 3 - 2x
\]
Now, the slope-intercept form of the first equation is:
\[
y = -2x + 3
\]
To create a second equation that has an infinite number of solutions, we can multiply the entire equation by a non-zero constant. A simple choice is to multiply by 2:
\[
2y = 2(-2x + 3)
\]
\[
2y = -4x + 6
\]
Now we rearrange it back to slope-intercept form:
\[
2y = -4x + 6
\]
Divide everything by 2:
\[
y = -2x + 3
\]
However, we can also express the same line differently. For example, if we multiply the original equation by \(\frac{1}{2}\):
\[
\frac{1}{2}(6x + 3y) = \frac{1}{2}(9)
\]
This results in:
\[
3x + \frac{3}{2}y = \frac{9}{2}
\]
Rearranging it to slope-intercept form leads to:
\[
\frac{3}{2}y = -3x + \frac{9}{2}
\]
Divide by \(\frac{3}{2}\):
\[
y = -2x + 3
\]
Thus, the simplest way to write a second equation that will also have an infinite number of solutions is simply to use the same line again, or a proportional modification. One example of a second equation in the slope-intercept form could simply be the same as above:
\[
y = -2x + 3
\]
So we can write:
The second equation could be \( y = -2x + 3 \).